Representasi Perempuan dalam Proses Legislasi:Catatan Sejarah Undang-Undang Nomor 46 Tahun 1946 dan Undang-Undang Nomor 1 Tahun 1974 - ‎ ‎, Mufliha Wijayati (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
This Article explain the involvement of women’s organization in the legislation process of marriage regulations in Indonesia. The research data for this study was obtained from a literature review on history of Islamic Family law reform in Indonesia and an examination of the surrounding historical context. The involvement of women in the legislative process aims to ensure that regulations on marriage and divorce in Law number 22 of 1946 ang Law number 1 of 1974 do not result in discrimination and violence againt women but instead provide protection and equality for all parties involved. Trough astudy of literature on family law reform, specially regarding divorce regulations, this article enables readers to understand that the struggle for justice and equality in family relations must continue beyond the legislative process and extend to the implementation level, as well as efforts to improve the reforms.